Photochemical and antioxidant behavior of rice in response to water deficit - SUN Jun-wei; YANG Yong; JIANG De-an (浙江大学学报. 农业与生命科学版)
The effects of water deficit on photochemical parameters and activities of superoxide dismutase (SOD), catalase (CAT), peroxidase (POD) were investigated in two cultivars of rice. The soil water content fell to about 40% of field water capacity after withholding irrigation for 14 d. As a result, the net photosynthetic rate (Pn) was significantly depressed in both cultivars. The maximum photochemical efficiency (Fv/Fm) remained unchanged. The photochemical quenching coefficient (qP) and the actual quantum yield of electron transport rate of PS Ⅱ (ΦPSⅡ) in cultivar IR 1552 were not different between plants under water deficient condition and the irrigated control, but their SOD, CAT and POD activities of the drought-stressed plants were significantly higher.. However, those photochemical parameters in cultivar Azucena were significantly lower after withholding irrigation and all antioxidant enzyme activities decreased. The results indicated that there was different response to water stress between two rice cultivars.